Análise e simulação da cinética das reações de extinção e caustificação a partir de diferentes cales - Fernanda Ribeiro dos Santos (2021)
Lime is one of the oldest products to be produced and is currently applied in several industrial sectors, including the cellulose sector. In the cellulose industry that employs the Kraft process, lime is responsible for the recovery of sodium hydroxide (the main chemical compound in white liquor) from the extinction and causticization reactions. Through the lime mud, generated after the reactions, it is possible to recover the lime and start a new cycle. The replacement of this input is necessary, since there are losses during the process and reduced reactivity. Based on this, the present work aims to study the parameters related to the recovery stage of the Kraft process, seeking to elucidate the important factors that affect the reactions of extinction and causticization of lime. The experiment planning method was applied in order to find the relationship between lime granulometry factors (0 to 3 mm, 3 to 19 mm and 19 to 40 mm) and lime ratio (60, 85, 110 g / L) through statistical analysis. The temperature profiles obtained from monitoring the reactions over time were a source of data to feed the simulator and, thus, find parameters related to the kinetics of these reactions. It was found by the standard reactivity analysis that the reactivity of the limes and the size of the particles formed after the reaction with the water were inversely proportional. In the reproduction of the reactions in the laboratory, the largest limes (3 to 19 and 19 to 40 mm) showed greater temperature variation (18.26 ° C and 18.44 ° C), as expected. The highest causticization efficiency found was 87.36%, showing a higher value than that practiced in industrial units. Through the design of experiments, it was found that the granulometry and the lime ratio influence the measured temperature variation, and the lime ratio has a greater effect on the temperature variation in relation to the granulometry. It was also identified that in the reaction of lime with green liquor the interaction between the factors also has an effect on the temperature. Through the simulation it was evaluated the variation of enthalpy, the diffusion coefficient and the activation energy of these reactions that could be compared to the data in the literature, showing to be coherent. The simulator showed good adjustments to the experimental data, presenting less than 5% of experimental error. Thus, the work presents interesting results that contribute to the expansion of knowledge about the use of lime in the Kraft process.